The heat capacity of nitrogen chain in grooves of single-walled carbon nanotube bundles - Bagatskii, M.I.; Barabashko, M.S.; Sumarokov, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The heat capacity of bundles of closed-cap single-walled carbon nanotubes with one-dimensional chains of nitrogen molecules adsorbed in the grooves has been first experimentally studied at temperatures from 2 to 40 K using an adiabatic calorimeter. The contribution of nitrogen CN2 to the total heat capacity has been separated. In the region 28 K the behavior of the curve CN2(T) is qualitatively similar to the theoretical prediction of the phonon heat capacity of 1D chains of Kr atoms localized in the grooves of SWNT bundles. Below 3 K the de-pendence CN2(Т) is linear. Above 8 K the dependence CN2(Т) becomes steeper in comparison with the case of Kr atoms. This behavior of the heat capacity CN2(Т) is due to the contribution of the rotational degrees of free-dom of the N2 molecules.